Kinematic/dynamic indicators of breaststroke technique of junior swimmers - Ryabchuk, V.; Ponimasov, O.; Titarenko, Y.; Lyashenko, O. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to test benefits of the new swimming technique excellence training model for the 10-11-year-old breaststroke groups facilitated by integrated structuring of special technical indicators of physical fitness.Methods and structure of the study. In the new swimming technique excellence training model testing experiment, we combined and analyzed benefits of the integrated structuring of special technical indicators of physical fitness to facilitate progress of the sample. We sampled for the tests the 10.5 ± 0.4 year-old swimmers (n=42, 24 boys and 18 girls) and split them up into Reference (RG, 10 boys and 8 girls) and Experimental (EG, 14 boys and 10 girls) Groups. The integrated train-ing model was geared to offer the most efficient combinations of training methods, tools and aspects for fast competitive progress facilitated by the integrated structuring of special technical indicators of physical fitness. The elementary technical progress was harmonized with the physical qualities building elements to prudently sequence the training stages for suc-cess. The progress tests enabled us to develop a set of the age-group progress benchmarks and test benefits of the inte-grated structuring of special technical indicators of physical fitness tests for efficiency of the breaststroke excellence model.Experimental assumptions and effects were verified by the strength, physical fitness and swimming technique rating tests in practical trainings. Results and conclusion. The new swimming technique excellence training model for the 10-11-year-old breaststroke groups facilitated by the integrated structuring of special technical indicators of physical fitness was found beneficial for competitive progress and in many other aspects including metabolic plastic transformations due to synchronization of en-dogenous processes.